Enhancing Cilnidipine Solubility Using Co-amorphous Formulation with L-Tryptophan: Molecular Docking, Physicochemical Characterization, and Development of Optimized Fast-dissolving Tablets - Dr. Jitendra Gupta (Asian Journal of Pharmaceutics (AJP), 2025)
Cilnidipine (CIL), is a calcium channel blocker and a Biopharmaceutics Classification System Class II drug, exhibits poor aqueous solubility. The study aimed to enhance CIL’s solubility through the development of a co-amorphous (COAM) system using L-tryptophan (1:1 molar ratio). Molecular docking was employed before formulation to investigate interactions, such as hydrogen bonding, π-π and σ-π stacking, confirming a strong binding affinity between CIL and the amino acids. The COAM system was prepared using the solvent evaporation method, and subsequently characterized using Fourier transform infrared spectroscopy, Differential scanning calorimetry, X-ray powder diffraction, 1 H-Nuclear Magnetic Resonance spectroscopy and scanning electron microscopy. COAM formulation significantly improved solubility by 15.75-fold (81.766 ± 0.5 mg/mL) compared to pure CIL (5.19 ± 0.07 mg/mL) attributed to its transformation into an amorphous state, associated decrease in heat flow and protonation effects. Fast-dissolving tablets (FDTs) incorporating the COAM were developed via direct compression and optimized using a Box-Behnken Design to evaluate essential formulation parameters. The FDTs (F1–F15) demonstrated acceptable physicochemical properties, including uniform weight (99.69 ± 7.47–103.87 ± 6.25 mg), hardness (2.48 ± 0.78–2.67 ± 0.56 kg/cm²), friability (<1%), thickness (3.52 ± 0.14–3.59 ± 0.15 mm), drug content (92 ± 0.16–99 ± 0.78%), and disintegration time (61 ± 2.02–87 ± 1.12 s). The optimized formulation (F14) exhibited rapid disintegration (61 ± 2.02 s) and the highest drug release (94.86 ± 0.29%). This research highlights the potential of COAM for improving the delivery of poorly soluble drugs in the pharmaceutical industry.